Significance of Single-Nucleotide Polymorphisms in mTOR (rs11204981) and ATG5 (rs510432) Genes in Allergic Diseases in Children - O.P. Volosovets; V.Ye. Dosenko; S.P. Kryvopustov; O.V. Pavlyk; O.V. Yeemets; D.O. Stroi (Zaslavsky O.Yu., 2015)
The objective of this study - to determine the association between single-nucleotide polymorphisms in mTOR (mammalian target of rapamycin) and ATG5 (autophagy related gene 5) genes and allergic phenotype in children. Genotyping for mTOR (rs11121704) and ATG5 (rs510432) was performed in group of patients with atopic diseases and in control group using real-time polymerase chain reaction. We have found that 50 (54.9 %) patients and 43 (49.4 %) healthy children had major allele (TT) of rs11121704 polymorphism; 36 (39.6 %) and 32 (36.8 %), respectively, had heterozygous allele (TC); 5 (5.5 %) and 12 (13.8 %) had minor allele (CC). Variants with CC genotype of rs11121704 in mTOR gene were revealed 2.5 times more frequently in the control group than among patients. Allelic variants in ATG5 gene were as follows: 51 (52 %) patients and 43 (44.3 %) healthy children had heterozygous allele (CT), 29 (29.6 %) and 21 (21.6 %), respectively, had minor allele (TT), and 18 (18.4 %) and 33 (34 %) had major allele (CC). TT genotype is associated with increased risk of early manifestation of bronchial asthma (until 3 years of life). We believe that polymorphisms in mTOR (rs11121704) and ATG5 (rs510432) genes may serve as important predictive markers in evaluating the risk of bronchial asthma and other allergic diseases in children.